Polemik Pemberian Hukuman Mati Pelaku Korupsi di Tengah Pandemi Covid-19 - Anisa Mufida (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract:The issue of corruption is a crime that is already familiar in today's society. Especially during the current pandemic, corruption is very vulnerable to being committed by irresponsible persons. In fact, all of that has been warned that corruption in the midst of disaster conditions will receive threats and demands for the death penalty. As for several sectors that span corruption there are at four points, such as the procurement of goods and services, the contribution of third parties, the allocation of budget from the APBN and APBD; both the allocation of regional expenditure resources and the use of the budget, as well as the distribution of social assistance programs in the framework of social safety net.Keywords: Corruption, Demands, Social Assistance Abstrak:Isu korupsi merupakan tindak pidana yang sudah tidak asing lagi di tengah masyarakat saat ini. Apalagi saat pandemic saat ini, maka kejahatan korupsi sangat rentan dilakukan oleh para oknum yang tidak bertanggung jawab. Padahal, semua itu sudah diwanti-wanti bahwa korupsi di tengah kondisi bencana akan mendapatkan ancaman dan tuntutan hukuman mati. Adapun beberapa sektor yang rentang terhadap korupsi terdapat pada empat titik, seperti sektor pengadaan barang dan jasa, sektor sumbangan dari pihak ketiga, pengalokasian anggaran dari APBN maupun APBD; baik itu alokasi sumber daerah belanja maupun pemanfaatan anggaran, serta pendistribusian program bantuan sosial dalam rangka social safety net.Kata Kunci: Korupsi, Tuntutan, Bantuan Sosial